Goya - Francois; Chabrum, Jean (Barcelona : Ediciones Daimon, 1970)
Contiene: la vida oscura 1746-1792, la vida ardiente 1792-1808, el caos, la sociedad y la gloria 1808-1828
Keywords: ARTES VISUALES; PINTURA